DAMPAK PENERAPAN LATIHAN TABATA TERHADAPPENINGKATAN KEMAMPUAN KECEPATAN (SPEED)(Studi Eksperimen pada Atlet Futsal PuteriAnggota UKM Futsal UPI Bandung) - Nurkarmila, Mila (2015)
Dalamlatarbelakangpenelitianinimembahaskomponenfisikkecepatan(speed).Ada beberapapolalatihanuntukmengembangkanataumeningkatkankecepatan(speed), salahsatunyaadalahpelatihanTabata.Permasalahan yang penulisajukanpadapenelitianinimengenaidampakpenerapanpelatihanTabataterhadappeningkatankemampuankecepatan(speed).TujuandalampenelitianiniuntukmelihathasildaripenerapanpelatihanTabataterhadappeningkatankemampuankecepatan(speed).Metode yang diguakanyaitumetodeeksperimen.Populasidalampenelitianinisebanyak 32 orang anggota UKM Futsal Puteri UPI, tekniksampling yang digunakanyaitusampling purposive, sampel yang diambil 18 orang yang dipilihsebagaisuatukebutuhantim.Pengumpulan data menggunakan instrument 20 meter dash sprint.Dari hasilperhitunganstatistikdari data pre-testdanpost-test, denganmenggunakanujikesamaandua rata-rata (skorberpasangan). Dari hasilpengolahandananalisis data diperoleh rata-rata test meningkatdari3,65menjadi 3,53. KesimpulandaripenelitianinibahwapelatihanTabatamemberikandampak yang signifikanterhadappeningkatankemampuananaerobikyaitukemampuankecepatan(speed). The background of this study isdiscuss physical component speed. There are some pattern exercises to develop or to increase speed capability, one of them is tabata training. The problems that proposed by the author on this study is the impact of the application of training tabata on increasing speed capability. An objective of this research is to see the result of the application of tabata training on increasing speed capability. This research used an experimental methods. The respondents of this study are 32 members of woman futsal of Indonesia University of Education, the sampling technique used is sampling purposive , 18 person are taken and they are chosen because of the needs on that team. To collect the data the researcher used 20 meters dash sprints as an instrument of the test. The result of calculation of statistics from pre-test and post-test data , by using two tests in equality of the average score ( pairs score ). The result of the processing and analysis of data collection is the test increased from 3.65 to 3.53. The conclusion of this research is tabata training can increase significant impact on the anaerobic skill,one of that skill is speed capability.